A Life on the Path of Knowledge: Rifa‘at ‘Ali Abou-El-Haj - Blumi, Isa (Kadim, 2022)
Rifa‘at ‘Ali Abou-El-Haj (1933-2022), a scholar of the Early Modern Ottoman Empire, completed a Ph.D. in Princeton University’s Departments of Oriental Studies and History in 1963. A key member of a generation of scholars who challenged a Euro-American dominated academy and its study of the Middle East, Dr. Abou-El-Haj spent the majority of his teaching career at California State University, Long Beach. For over 50 year, Abou-El-Haj critically engaged scholars working on the early modern Ottoman state and society via publications such as The 1703 Rebellion and the Structure of Ottoman Politics (Leiden: Brill, 1984; translated into Turkish in 2011) and Formation of the Modern State: The Ottoman Empire, Sixteenth to Eighteenth Centuries (Albany: SUNY University Press, (1991; in translated into Turkish in 2018)